Hemistepsin A suppresses colorectal cancer growth through inhibiting pyruvate dehydrogenase kinase activity - Ling Jin (Nature Portfolio, 2020)
Abstract Most cancer cells primarily produce their energy through a high rate of glycolysis followed by lactic acid fermentation even in the presence of abundant oxygen. Pyruvate dehydrogenase kinase (PDK) 1, an enzyme responsible for aerobic glycolysis via phosphorylating and inactivating pyruvate dehydrogenase (PDH) complex, is commonly overexpressed in tumors and recognized as a therapeutic target in colorectal cancer. Hemistepsin A (HsA) is a sesquiterpene lactone isolated from Hemistepta lyrata Bunge (Compositae). Here, we report that HsA is a PDK1 inhibitor can reduce the growth of colorectal cancer and consequent activation of mitochondrial ROS-dependent apoptotic pathway both in vivo and in vitro. Computational simulation and biochemical assays showed that HsA directly binds to the lipoamide-binding site of PDK1, and subsequently inhibits the interaction of PDK1 with the E2 subunit of PDH complex. As a result of PDK1 inhibition, lactate production was decreased, but oxygen consumption was increased. Mitochondrial ROS levels and mitochondrial damage were also increased. Consistent with these observations, the apoptosis of colorectal cancer cells was promoted by HsA with enhanced activation of caspase-3 and -9. These results suggested that HsA might be a potential candidate for developing a novel anti-cancer drug through suppressing cancer metabolism.